Skinner’s Presence in Brazilian Behavior-Analytic Articles (1961 – 1998) (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
The goal of this study was to extend that analysis to behavior-analytic articles published from 1961 to 1998. The sources of information were original articles based on Behavior Analysis, published in Brazilian journals. From the 302 articles selected, a total of 5789 references were found 351 of which were references to Skinner (6,1% of total). Most of the analyzed articles did not present any reference to Skinner and most of Skinner’s publications were not cited during that period. It can be said that there’s a frequent presence of Skinner in the literature but this presence took place through uneven access to his work.
Keywords: Behavior Analysis; bibliometric analysis; B. F. Skinner; history of psychology; scientific communication; scientometry